(untitled) (Eurasian Medical Research Periodical, 2022)
Pneumonia as an independent disease and complicating process remains one of the most frequent and threatening infections. In spite of introduction into practice of highly effective antibacterial preparations, pronounced tendency to increase of unfavorable outcomes of pneumonia, especially in children and persons of working age, testifies to qualitative change of the disease in modern conditions[11]. Currently, the species spectrum of infectious complications, acute and nosocomial bacterial pneumonia and sepsis has changed drastically. This has been facilitated by an increased incidence of congenital and acquired immunodeficiency states, due to various endogenous and exogenous factors[3,9,12].